Hypertension the major predictor of mortality in COVID-19: A retrospective study - Rizka Febtrina; Andre Syahputra; Eka Malfasari; Dendy Kharisna (Journal of the Pakistan Medical Association)
Objective: To determine the role of comorbid diseases in patients with coronavirus disease-2019. Method: The quantitative, retrospective study was conducted in July 2022 at Arifin Achmad Hospital, Riau, Indonesia, and comprised patients who died due to coronavirus disease-2019 between January and March 2021. Data was retrieved from the institutional medical records using a checklist that contained items related to demographic and comorbid data. Data was analysed using SPSS 27. Results: Of the 48 patients, 27(56.3%) were males, 21(43.7%) were females, and 20(41.7%) were aged 45-60 years. There were 16(33.3%) patients having hypertension, 11(22.9%) had diabetes mellitus, 5(10.4%) had both hypertension and diabetes mellitus, 5(10.4%) had asthma, and there was no co-morbidity in 11(22.9%) patients. Conclusion: Hypertension was the most common comorbid disease among coronavirus disease-2019 who died. Keywords: Hypertension, Diabetes Mellitus, Morbidity, Asthma, Demography.